Propylene polymerization sphere-like catalyst component, solid titanium main catalyst and preparation method and application of solid titanium main catalyst

By using industrially readily available benzoate peroxide compounds as internal electron donors, combining solid titanium main catalysts and alkyl aluminum compounds to form spherical catalyst components, the problems of difficulty in synthesis and high production costs of existing electron donor compounds are solved, and efficient catalytic propylene polymerization is achieved to produce high-quality polymers.

CN119638873AActive Publication Date: 2025-03-18JILIN TIANLONG CATALYST CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411902319.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-18
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

The electron donor compounds of existing propylene polymerization Ziegler-Natta catalysts have problems with synthesis difficulties, high production costs and potential harm to the human body and the environment.

Method used

An industrially readily available benzoate peroxide compound is used as an internal electron donor, and a solid titanium main catalyst and an alkyl aluminum compound cocatalyst is combined to form a spherical catalyst component.

Benefits of technology

The catalyst component exhibits high catalytic activity, good stereotactic ability, hydrogen adjustment sensitivity and copolymerization performance, and can produce propylene polymers with high aberrations, good particle morphology, high apparent density and few fine powders, and improve the processing performance of the polymer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005203524060000021
    Figure BDA0005203524060000021
  • Figure BDA0005203524060000031
    Figure BDA0005203524060000031
  • Figure BDA0005203524060000091
    Figure BDA0005203524060000091
Patent Text Reader

Abstract

The invention provides a propylene polymerization sphere-like catalyst component, a solid titanium main catalyst and a preparation method and application of the solid titanium main catalyst, the solid titanium main catalyst comprises titanium halide, magnesium halide and peroxidated benzoate internal electron donors, and under the action of an alkyl aluminum cocatalyst and an organosilicon compound external electron donor, the solid titanium main catalyst is prepared into the sphere-like catalyst component. The catalyst is used for propylene polymerization or copolymerization, shows very high polymerization activity, very good hydrogen regulation sensitivity and stereospecificity, can be used for preparing a green and environment-friendly propylene polymer with high polymer isotacticity, good particle morphology and less fine powder, and can be used for producing a polypropylene product with a high melt index.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of catalysts, and relates to a solid Ziegler-Natta catalyst for propylene polymerization or copolymerization, a preparation method and an application thereof in catalyzing propylene polymerization or copolymerization reactions. Specifically, it relates to a catalyst component and a catalyst using a magnesium compound as a carrier and an electron donor with a specific chemical structure. Background Art

[0002] Polypropylene material has the characteristics of low relative density, good mechanical properties, good molding and processing performance, high heat resistance, good chemical properties, pure and non-toxic texture, etc. The polymer particles made from it have important applications in fiber products, medical equipment, automobiles, bicycles, parts, pipelines, chemical containers, food, and pharmaceutical packaging. The catalyst that catalyzes propylene polymerization is the key to affecting the performance of polypropylene materials.

[0003] Since the discovery of Ziegler-Natta catalysts and their application in industrial production of polypropylene, after more than 60 years of research and development, polypropylene catalysts have developed from the first generation to the fifth generation, from the initial low-activity complex catalysts to the current high-activity, spherical or quasi-spherical catalysts. In the development process of propylene polymerization catalysts, it is the continuous use of new electron donor compounds that drives their renewal, giving propylene polymerization catalysts higher activity and better stereospecific ability, so that the obtained polypropylene materials have better performance. Therefore, it can be said that electron donor compounds are the core of polypropylene catalysts. Initially, researchers added ethyl benzoate or phthalate as internal electron donors of propylene polymerization catalysts during the preparation of Ziegler-Natta catalysts to form solid titanium catalysts, and added another electron donor (alkoxysilane compound) during olefin polymerization. When catalyzing propylene polymerization, highly isotactic polypropylene was obtained, indicating that the addition of electron donor compounds greatly improved the stereospecific ability of the catalyst. Since then, research on internal and external electron donors has also become the core technology for the development of propylene polymerization Ziegler-Natta catalysts. At present, a series of aliphatic dicarboxylic acid esters have been reported in China as electron donors for propylene polymerization Ziegler-Natta catalysts, among which succinate esters have the best performance and the molecular weight distribution of the resulting polymer is relatively wide. Catalysts with succinate compounds as internal electron donors have high stereospecific properties; and their greatest feature is that the polypropylene obtained has a very wide relative molecular weight distribution, which improves the processing performance of polypropylene. Products that could only be produced by multi-reactor processes before can be produced by polymerization in a single reactor, and the products are high-rigidity homopolymers and multiphase copolymers, which expand the performance of propylene homopolymers and copolymers. Some patents also report that diol ester compounds can be used as electron donors for propylene polymerization Ziegler-Natta catalysts, which are characterized by wide molecular weight distribution, high catalytic activity, easy adjustment of stereospecific properties, high isotacticity of the polypropylene obtained without adding external electron donors, and wide relative molecular weight distribution. Some patents also report that magnesium halides, titanium compounds and organic diethers or polyethers can be combined, such as using l,3-diether as an electron donor compound to prepare a catalyst. During polymerization, this catalyst system can obtain highly isotactic polypropylene without adding an external electron donor and has high activity.

[0004] The use of the above electron donor compounds gives the solid titanium catalyst better catalytic performance, but there are also certain disadvantages. For example, phthalate ester electron donors can cause certain harm to the human body and the environment, and succinate esters, diol esters and diether electron donors have problems such as difficult synthesis, long synthesis route and high production cost. Therefore, it is necessary to continue to study the electron donor compounds of propylene polymerization Ziegler-Natta catalysts. Summary of the invention

[0005] In view of the above technical problems and defects, the object of the present invention is to provide a spherical catalyst component for propylene polymerization, in which the internal electron donor is a peroxybenzoic acid ester compound that is easily available in industry, which can overcome the problems of difficult synthesis and high production cost of the above electron donor; in addition, the catalyst prepared by using the peroxybenzoic acid ester compound as the internal electron donor shows high catalytic activity, high stereospecific ability, good hydrogen sensitivity, copolymerization performance and sensitivity to reaction temperature when catalyzing olefin polymerization. After being used for propylene polymerization, a green and environmentally friendly propylene polymer with high polymer isotacticity, good particle morphology, high apparent density and less fine powder can be produced, and can be used to produce polypropylene products with a high melt index.

[0006] To achieve the above object, the present invention adopts the following technical solution:

[0007] A spherical catalyst component for propylene polymerization, comprising a solid titanium main catalyst, an alkyl aluminum compound co-catalyst and / or an external electron donor compound; wherein the solid titanium main catalyst comprises any one or a mixture of two or more of magnesium or magnesium halide or alkyl magnesium or alkoxy magnesium, a liquid titanium compound and an internal electron donor compound;

[0008] The internal electron donor compound is selected from one or more compounds having the structure of formula (I):

[0009]

[0010] In the formula, R is selected from H atoms, halogens, C1~C 20 The term "alkyl" refers to a linear or branched alkyl, alkenyl, cycloalkyl, aryl, arylalkyl or alkylaryl group.

[0011] As a preferred embodiment of the present invention, the alkyl aluminum compound co-catalyst has the general formula of AlR 1 n X 3-n , where R 1 Is the same or different C1~C 20 Alkyl, including linear, branched or cyclic alkyl, X is halogen, n = 1, 2 or 3;

[0012] The external electron donor compound is a compound of the general formula R n Si(OR ’ ) 4-n An organosilicon compound, wherein 0≤n≤3, R and R ’ are the same or different alkyl, cycloalkyl, aryl, or halogenated alkyl groups; or, R is a halogen or a hydrogen atom.

[0013] As a preferred embodiment of the present invention, the ratio between the solid titanium main catalyst, the alkyl aluminum compound co-catalyst and the external electron donor compound is, based on the molar ratio of titanium, the amount of the alkyl aluminum compound co-catalyst is 5 to 1000 moles; based on the molar ratio of aluminum, the amount of the external electron donor compound is 0.025 to 1.0 mole.

[0014] As a preferred embodiment of the present invention, the magnesium is micron-sized spherical magnesium particles; the magnesium halide is selected from magnesium dihalide, water or alcohol complexes of magnesium dihalide, and derivatives of magnesium dihalide in which one halogen atom is replaced by a hydrocarbon group or a hydrocarbon oxygen group; the alkyl magnesium includes diethyl magnesium, di-n-butyl magnesium, and di-n-hexyl magnesium, and the alkoxy magnesium includes ethoxy magnesium.

[0015] As a preferred embodiment of the present invention, the liquid titanium compound should be a liquid compound that is completely soluble in a non-polar solvent at the application temperature, and the general formula of the liquid titanium compound is Ti(OR): 4-a X a , in the general formula, R is C1~C 10 wherein X is selected from F, Cl, and Br, and a is an integer of 1 to 4. The amount thereof is 0.5 to 150 moles per mole of magnesium halide.

[0016] As further preferred embodiment of the present invention, the alkyl aluminum compound co-catalyst is selected from any one of triethyl aluminum, triisobutyl aluminum, tri-n-butyl aluminum, tri-n-hexylaluminum, and alkyl aluminum chloride, or a mixture of two or more thereof.

[0017] As a further preferred embodiment of the present invention, the magnesium halide is selected from any one of magnesium dichloride, magnesium dibromide, phenoxymagnesium chloride, isopropoxymagnesium chloride, butoxymagnesium chloride, or a mixture of two or more thereof, preferably magnesium dichloride.

[0018] As a further preferred embodiment of the present invention, the liquid titanium compound is selected from one or a mixture of two or more of titanium tetrachloride, titanium tetrabromide, titanium tetraiodide, titanium tetrabutoxide, titanium tetraethoxide, titanium triethoxide monochloride, titanium diethoxide dichloride, titanium trichloride monoethoxide, preferably titanium tetrachloride.

[0019] As a further preference of the present invention, the internal electron donor compound is selected from any one of benzoic acid peroxide, methyl perbenzoate, ethyl perbenzoate, isopropyl perbenzoate, tert-butyl perbenzoate, tert-hexyl perbenzoate, and tert-amyl perbenzoate, or a mixture of two or more thereof; the internal electron donor compound is used in an amount of 0.10 to 0.50 mole per mole of magnesium halide.

[0020] The present invention also provides a solid titanium main catalyst for propylene polymerization or copolymerization, comprising any one or a mixture of two or more of magnesium or magnesium halide or alkyl magnesium or alkoxy magnesium, a liquid titanium compound and an internal electron donor compound; wherein the internal electron donor compound is selected from one or more compounds having a structure of formula (I):

[0021]

[0022] In the formula, R is selected from H atoms, halogens, C1~C 20 The term "alkyl" refers to a linear or branched alkyl, alkenyl, cycloalkyl, aryl, arylalkyl or alkylaryl group.

[0023] As a preferred embodiment of the present invention, the magnesium is micron-sized spherical magnesium particles; the magnesium halide is selected from magnesium dihalide, water or alcohol complex of magnesium dihalide, and a derivative of magnesium dihalide in which a halogen atom is replaced by a hydrocarbon group or a hydrocarbon oxide group; the alkyl magnesium includes diethyl magnesium, di-n-butyl magnesium, and di-n-hexyl magnesium, and the alkoxy magnesium includes ethoxy magnesium;

[0024] The liquid titanium compound should be a liquid compound that is completely soluble in a non-polar solvent at the application temperature. The general formula of the liquid titanium compound is Ti(OR): 4-a X a , in the general formula, R is C1~C 10 wherein X is selected from F, Cl, and Br, and a is an integer of 1 to 4.

[0025] As a preferred embodiment of the present invention, the solid titanium main catalyst also includes an alkyl aluminum compound, and the alkyl aluminum compound includes alkyl aluminum compounds such as trimethyl aluminum, triethyl aluminum, triisobutyl aluminum, and diethyl aluminum monochloride.

[0026] The present invention also provides a method for preparing a solid titanium main catalyst for propylene polymerization or copolymerization, the method comprising the following steps:

[0027] Step 1. dissolving any one of magnesium, magnesium halide, alkyl magnesium or alkoxy magnesium, or a mixture of two or more thereof in a solvent system containing an organic alcohol to form a uniform solution;

[0028] Step 2. Adding a liquid titanium compound, the contact reaction temperature of the liquid titanium compound and the magnesium halide solution is controlled at -40 to 0°C to ensure that the titanium / magnesium active component is a uniform solution, and the amount of the titanium compound added is 1 to 50 mol per mole of magnesium halide, preferably 4 to 40 mol;

[0029] Step 3. The mixed solution of step 2 is heated, and an internal electron donor compound for adjusting the activity of the catalyst, hydrogen sensitivity and polymer regularity is added, and then an alkyl aluminum compound is added or not added, and the temperature is continued to be heated, and solid titanium main catalyst particles are precipitated by stirring, so that the titanium content of the obtained solid titanium main catalyst is between 0.5 and 4.0%; the magnesium content is between 5.0 and 20.0%; the content of the internal electron donor compound is between 5.0 and 15.0%, and the specific surface area of ​​the catalyst is between 100 and 500 m 2 / g, and the pore volume is between 0.5 and 1.5 mL / g;

[0030] or,

[0031] Step 1. dissolving any one of magnesium or magnesium halide or alkyl magnesium or alkoxy magnesium or a mixture of two or more thereof in a solvent system containing an organic alcohol to form a uniform solution; then adding an internal electron donor compound for adjusting the activity of the catalyst, hydrogen sensitivity and polymer regularity to the uniform solution;

[0032] Step 2. Adding a liquid titanium compound, the contact reaction temperature of the liquid titanium compound and the magnesium halide solution is controlled at -40 to 0°C to ensure that the titanium / magnesium active component is a uniform solution, and the amount of the titanium compound added is 1 to 50 mol per mole of magnesium halide, preferably 4 to 40 mol;

[0033] Step 3. The mixed solution of step 2 is heated, with or without adding an alkyl aluminum compound, and then the temperature is continued to be heated, and solid titanium main catalyst particles are precipitated by stirring, so that the titanium content of the obtained solid titanium main catalyst is between 0.5 and 4.0%; the magnesium content is between 5.0 and 20.0%; the content of the internal electron donor compound is between 5.0 and 15.0%, and the specific surface area of ​​the catalyst is between 100 and 500 m 2 / g, and the pore volume is between 0.5 and 1.5 mL / g.

[0034] As preferred embodiments of the present invention, the organic alcohol is a straight-chain or branched alkyl alcohol or cycloalkanol having 1 to 10 carbon atoms, an aromatic alcohol or aromatic alkanol having 6 to 20 carbon atoms, and halides of the above organic alcohols, including methanol, ethanol, propanol, isopropanol, butanol, pentanol, hexanol, 2-methylpentanol, 2-ethylbutanol, heptanol, 2-ethylhexanol, octanol and decanol; the organic alcohols are used alone or in combination, wherein the amount of the organic alcohol compound is 0.1 to 10.0 moles per mole of magnesium halide.

[0035] As a preferred embodiment of the present invention, one or more inert diluents are optionally added to the solvent system described in step 1, and the inert diluents include hexane, heptane, octane, decane, benzene, toluene, xylene, 1,2-dichloroethane, chlorobenzene and other hydrocarbons or halogenated hydrocarbon compounds, as long as they are helpful for dissolving the magnesium halide, they can be used; the dissolution temperature is controlled between 10 and 150° C., and the dissolution can also be carried out at a certain temperature and pressure, and the dissolution time is based on complete dissolution.

[0036] When preparing the solid titanium main catalyst of the present invention, solid catalyst particles are precipitated during the heating process of the reaction system. The heating speed can be fast or slow to adjust the particle size of the catalyst, and the temperature should be controlled below the boiling point of the solvent. The internal electron donor compound can be added during the heating process of the contact reaction between the liquid titanium compound and the magnesium halide solution, or can be added to the organic alcohol solution of the magnesium halide, and can be added once or in batches for multiple times.

[0037] The formed catalyst particles can be subjected to conventional washing, drying and other steps to obtain a fluid solid powder catalyst. In addition, in order to adjust the titanium content in the catalyst, the catalyst particles can also be washed once or multiple times.

[0038] The spherical catalyst component for propylene polymerization or the solid titanium main catalyst for propylene polymerization or copolymerization provided by the present invention can be used in the polymerization reaction of olefin CH2=CHR, wherein R is hydrogen or an alkyl or aryl group with 1 to 6 carbon atoms. When the above catalyst component or solid titanium main catalyst is used for the polymerization reaction of olefin, it can be carried out according to a known method, which can be liquid phase bulk polymerization, solution polymerization in which liquid phase monomer is dissolved in an inert solvent, gas phase polymerization, or a combined polymerization process of liquid phase bulk + gas phase, gas phase + gas phase is used for operation. The propylene polymerization temperature is generally 0°C to 150°C, preferably 60°C to 100°C, and the polymerization reaction pressure is normal pressure or high pressure.

[0039] Advantages and beneficial effects of the present invention:

[0040] (1) The solid titanium main catalyst provided by the present invention adopts an internal electron donor compound with a specific structure, so that the obtained catalyst has high polymerization activity and stereospecific ability; at the same time, it maintains the characteristics of narrow catalyst particle size distribution, good hydrogen adjustment sensitivity, large pore volume and large pore size, and can be used for olefin polymerization, and is suitable for slurry polymerization, bulk polymerization, bulk-gas phase combination and gas phase polymerization processes.

[0041] (2) When the solid titanium main catalyst provided by the present invention is used in combination with an alkyl aluminum compound co-catalyst and an external electron donor compound as a catalyst component, it has a strong sensitivity to the reaction temperature and can be used to produce polypropylene with a high melt index. At the same time, it can also make the molecular weight distribution of the obtained polypropylene product wider, thereby effectively improving the processing performance of the polypropylene product.

[0042] (3) The internal electron donor provided by the present invention is a peroxybenzoic acid ester compound that is easily available in industry, which can overcome the problems of difficult synthesis and high production cost of existing internal electron donors.

[0043] (4) In the present invention, an alkyl aluminum compound is added during the preparation process of the solid titanium main catalyst to 4+ Pre-reduction is performed to form Ti 3+ It has the advantages of being easy to coordinate with magnesium halide, being able to increase the activity of the main catalyst, and improving the polymerization reaction kinetics of the main catalyst; the obtained polymerization product has the characteristics of narrow molecular weight distribution and high melt index.

[0044] (5) The catalyst component provided by the present invention can be used to produce green and environmentally friendly propylene polymers with high polymer isotacticity, good particle morphology, high apparent density and less fine powder. DETAILED DESCRIPTION

[0045] In order to explain the present invention more clearly, the present invention is further described below in conjunction with preferred embodiments. It should be understood by those skilled in the art that the following specific description is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.

[0046] Example 1

[0047] 1. Synthesis of solid titanium main catalyst:

[0048] (1) In a glass bottle fully purged with high-purity nitrogen, 7.14 g (75 mmol) of anhydrous magnesium chloride, 37.5 ml of decane and 35.1 ml (225 mmol) of 2-ethylhexanol were added in sequence, and the above suspension was heated at 130° C. for 3 hours to obtain a uniform solution.

[0049] (2) The magnesium chloride alcoholate solution of step (1) was added dropwise to 200 ml (1.8 mol) of titanium tetrachloride solution maintained at -24°C.

[0050] (3) The mixed solution of step (2) is heated to 40°C for a certain period of time, 2.0 ml (7.5 mmol) of benzoic acid peroxide is added to the mixed solution, and then the temperature is raised to 110°C. After the temperature reaches 110°C, the mixture is stirred at the same temperature for 2 hours.

[0051] (4) Recover the generated solid by hot filtration; resuspend it in 200 ml of titanium tetrachloride, then heat it to 110°C, stir for 30 minutes, and filter it. The solid is first washed thoroughly with 110°C decane, and then washed with hexane at 60°C until no titanium compound is detected in the washing liquid. After drying, a solid titanium primary catalyst is obtained.

[0052] The analysis results of the solid titanium main catalyst are as follows: Ti, 2.3%; Mg, 17.1%; electron donor, 12.8%.

[0053] 2. Propylene polymerization: After the 2-liter stainless steel polymerization kettle was fully replaced with high-purity N2, 12.1 mg of the above-mentioned solid titanium main catalyst, 2.0 mmol of triethylaluminum, 0.1 mmol of methylcyclohexyldimethoxysilane (CHMDMS) were added, 1.0 L (standard volume) of hydrogen was added, and liquid propylene was added to 1.0 L; the temperature was raised to 70°C and the polymerization reaction was carried out for 1 hour. The catalyst analysis results are shown in Table 1, and the polymerization results are shown in Tables 2 and 3.

[0054] Example 2

[0055] 1. Synthesis of solid titanium main catalyst:

[0056] Except that methyl perbenzoate was used instead of benzoic acid peroxide, the other procedures were the same as in Example 1.

[0057] The analysis results of the solid titanium main catalyst are as follows: Ti, 2.4%; Mg, 16.9%; electron donor, 11.4%.

[0058] 2. Polymerization: Same as Example 1. The catalyst analysis results are shown in Table 1, and the polymerization results are shown in Tables 2 and 3.

[0059] Example 3

[0060] 1. Synthesis of solid titanium main catalyst:

[0061] Except that ethyl perbenzoate is used instead of benzoic acid peroxide, the other procedures are the same as in Example 1.

[0062] The analysis results of the solid titanium main catalyst are as follows: Ti, 2.1%; Mg, 18.4%; electron donor, 13.3%.

[0063] 2. Polymerization: Same as Example 1. The catalyst analysis results are shown in Table 1, and the polymerization results are shown in Tables 2 and 3.

[0064] Example 4

[0065] 1. Synthesis of solid titanium main catalyst:

[0066] Except that isopropyl perbenzoate was used instead of benzoic acid peroxide, the other procedures were the same as in Example 1.

[0067] The analysis results of the solid titanium main catalyst are as follows: Ti, 2.7%; Mg, 18.3%; electron donor, 12.6%.

[0068] 2. Polymerization: Same as Example 1. The catalyst analysis results are shown in Table 1, and the polymerization results are shown in Tables 2 and 3.

[0069] Example 5

[0070] 1. Synthesis of catalyst:

[0071] Except that tert-butyl perbenzoate is used instead of benzoic acid peroxide, the other procedures are the same as in Example 1.

[0072] The analysis results of the solid titanium main catalyst are as follows: Ti, 2.5%; Mg, 18.2%; electron donor, 12.8%.

[0073] 2. Polymerization: Same as Example 1. The catalyst analysis results are shown in Table 1, and the polymerization results are shown in Tables 2 and 3.

[0074] Example 6

[0075] 1. Synthesis of solid titanium main catalyst:

[0076] Except that tert-amyl perbenzoate is used instead of benzoic acid peroxide, the other procedures are the same as in Example 1.

[0077] The analysis results of the solid titanium main catalyst are as follows: Ti, 2.4%; Mg, 18.6%; electron donor, 12.5%.

[0078] 2. Polymerization: Same as Example 1. The catalyst analysis results are shown in Table 1, and the polymerization results are shown in Tables 2 and 3.

[0079] Example 7

[0080] 1. Synthesis of solid titanium main catalyst:

[0081] (1) In a glass bottle fully purged with high-purity nitrogen, 7.14 g (75 mmol) of anhydrous magnesium chloride, 37.5 ml of decane and 35.1 ml (225 mmol) of 2-ethylhexanol were added in sequence, and the suspension was heated at 130° C. for 3 hours to obtain a uniform solution; 2.0 ml (7.5 mmol) of isopropyl peroxybenzoate was added to the uniform solution, and the temperature was kept at 130° C. for 1 hour.

[0082] (2) The magnesium chloride alcoholate solution of step (1) was added dropwise to 200 ml (1.8 mol) of titanium tetrachloride solution maintained at -24°C.

[0083] (3) After heating the mixed solution of step (2) to 110°C within a certain period of time, stirring at the constant temperature for 2 hours.

[0084] (4) Recover the generated solid by hot filtration; resuspend it in 200 ml of titanium tetrachloride, then heat it to 110°C, stir for 30 minutes, and filter. The solid is first washed thoroughly with 110°C decane, then washed with hexane at 60°C until no titanium compound is detected in the washing liquid. After drying, a solid titanium primary catalyst is obtained.

[0085] The analysis results of the solid titanium main catalyst are as follows: Ti, 2.2%; Mg, 15.9%; electron donor, 13.3%.

[0086] 2. Propylene polymerization: After the 2-liter stainless steel polymerization kettle was fully replaced with high-purity N2, 12.3 mg of the above solid catalyst, 2.0 mmol of triethylaluminum, 0.1 mmol of methylcyclohexyldimethoxysilane (CHMDMS), 1 L (standard volume) of hydrogen, and liquid propylene were added to 1.0 L; the temperature was raised to 70°C and the polymerization was carried out for 1 hour. The catalyst analysis results are shown in Table 1, and the polymerization results are shown in Tables 2 and 3.

[0087] Example 8

[0088] 1. Synthesis of solid titanium main catalyst:

[0089] Except that the amount of benzoic acid peroxide used was 3.0 mL (11.25 mmol), the rest was the same as in Example 1.

[0090] The analysis results of the solid titanium main catalyst are as follows: Ti, 2.9%; Mg, 17.4%; electron donor, 12.8%.

[0091] 2. Polymerization: Same as Example 1. The catalyst analysis results are shown in Table 1, and the polymerization results are shown in Tables 2 and 3.

[0092] Example 9

[0093] 1. Synthesis of solid titanium main catalyst:

[0094] (1) In a glass bottle fully replaced with high-purity N2, 7.14 g (75 mmol) of anhydrous magnesium chloride, 0.5 g of spherical magnesium powder, 37.5 ml of decane and 35.1 ml (225 mmol) of 2-ethylhexanol were added in sequence, and the above suspension was heated at 130°C for 3 hours to obtain a uniform solution.

[0095] (2) The magnesium chloride alcoholate solution of step (1) was added dropwise to 200 ml (1.8 mol) of titanium tetrachloride solution maintained at -24°C.

[0096] (3) The mixed solution of step (2) was heated to 40° C. within a certain period of time, 2.0 ml (7.5 mmol) of isopropyl peroxybenzoate was added to the mixed solution, and then the temperature was raised to 110° C.; after the temperature reached 110° C., the mixture was stirred at the same temperature for 2 hours.

[0097] (4) Recover the generated solid by hot filtration; resuspend it in 200 ml of titanium tetrachloride, then heat it to 110°C, stir for 30 minutes, and filter it. The solid is first washed thoroughly with 110°C decane, and then washed with hexane at 60°C until no titanium compound is detected in the washing liquid. After drying, a solid titanium primary catalyst is obtained.

[0098] The analysis results of the solid titanium main catalyst are as follows: Ti, 2.6%; Mg, 16.6%; electron donor, 12.8%.

[0099] 2. Propylene polymerization: After the 2-liter stainless steel polymerization kettle was fully replaced with high-purity N2, 12.3 mg of the above solid catalyst, 2.0 mmol of triethylaluminum, 0.1 mmol of methylcyclohexyldimethoxysilane (CHMDMS), 1 L (standard volume) of hydrogen, and liquid propylene were added to 1.0 L; the temperature was raised to 70°C and the polymerization reaction was carried out for 1 hour. The catalyst analysis results are shown in Table 1, and the polymerization results are shown in Tables 2 and 3.

[0100] Example 10

[0101] 1. Synthesis of solid titanium main catalyst:

[0102] (1) In a glass bottle fully purged with high-purity nitrogen, 7.14 g (75 mmol) of anhydrous magnesium chloride, 37.5 ml of decane and 35.1 ml (225 mmol) of 2-ethylhexanol were added in sequence, and the above suspension was heated at 130° C. for 3 hours to obtain a uniform solution.

[0103] (2) The magnesium chloride alcoholate solution of step (1) was added dropwise to 200 ml (1.8 mol) of titanium tetrachloride solution maintained at -24°C.

[0104] (3) The mixed solution of step (2) is heated to 40° C. for a certain period of time, 2.0 ml (7.5 mmol) of isopropyl peroxybenzoate is added to the mixed solution, and then 5.0 ml (1.0 mmol / ml) of a decane solution of triethylaluminum is added dropwise to the mixed solution, and then the temperature is raised to 110° C.; after the temperature reaches 110° C., the mixture is stirred at the same temperature for 2 hours.

[0105] (4) Recover the generated solid by hot filtration; resuspend it in 200 ml of titanium tetrachloride, then heat it to 110°C, stir for 30 minutes, and filter it. The solid is first washed thoroughly with 110°C decane, and then washed with hexane at 60°C until no titanium compound is detected in the washing liquid. After drying, a solid titanium primary catalyst is obtained.

[0106] The analysis results of the solid titanium main catalyst are as follows: Ti, 3.0%; Mg, 16.6%; electron donor, 12.5%.

[0107] 2. Propylene polymerization: After the 2-liter stainless steel polymerization kettle was fully replaced with high-purity N2, 12.3 mg of the above solid catalyst, 2.0 mmol of triethylaluminum, 0.1 mmol of methylcyclohexyldimethoxysilane (CHMDMS), 1 L (standard volume) of hydrogen, and liquid propylene were added to 1.0 L; the temperature was raised to 70°C and the polymerization reaction was carried out for 1 hour. The catalyst analysis results are shown in Table 1, and the polymerization results are shown in Tables 2 and 3.

[0108] Comparative Example 1

[0109] 1. Synthesis of catalyst:

[0110] Except that diisobutyl phthalate was used instead of benzoic acid peroxide, the other steps were the same as in Example 1.

[0111] The analysis results of the solid titanium main catalyst are as follows: Ti, 3.2%; Mg, 17.1%; electron donor, 10.9%.

[0112] 2. Propylene polymerization: Same as Example 1, the catalyst analysis results are shown in Table 1, and the polymerization results are shown in Tables 2 and 3.

[0113] Table 1 Particle size distribution and diameter distance of catalyst

[0114]

[0115] Table 2 Polymerization results of catalysts

[0116]

[0117] Table 3 Screening results of polymer powder

[0118]

[0119] According to the data obtained from the above examples and comparative examples, it can be determined that the solid titanium main catalyst obtained by using the internal electron donor provided by the present invention has the characteristics of good particle morphology, narrow particle size distribution, good hydrogen adjustment sensitivity, less polymer fine powder, etc. The structure of the internal electron donor compound of the present invention has a specific peroxide structure and a carbonyl group and an ester group, wherein the carbonyl group and the ester group can coordinate with MgCl2, so that the effect of the internal electron donor and MgCl2 is stronger, wherein the peroxide-OO-structure is connected by two oxygen atoms through a non-polar covalent bond to form an ion group, and the two oxygen atoms share a pair of electrons, and each oxygen atom presents a 7-electron structure, and each oxygen atom needs to obtain an electron to achieve a stable structure of 8 electrons; especially when an oxygen molecule accepts an electron, a super-active ion structure is formed, and this structural feature promotes the coordination reaction activity of the carbonyl group, the ester group, the MgCl2, and the TiCl4, making its coordination stronger; it is not easy to be removed by the alkyl aluminum during the polymerization process, thereby improving the stereospecific ability of the solid titanium catalyst, and making the obtained polypropylene product have a wider molecular weight distribution and a higher melt index.

[0120] In the Ziegler-Natta catalyst system for propylene polymerization, the main function of the co-catalyst alkyl aluminum is to reduce tetravalent titanium to convert it into trivalent titanium to catalyze propylene polymerization. Trivalent titanium is the active center of the propylene polymerization catalyst. In the present invention, a certain amount of alkyl aluminum compound is added during the preparation of the solid titanium main catalyst to 4+ Pre-reduction is performed to form Ti 3+ It has the advantages of being easy to coordinate with magnesium halide and disperse in the main catalyst, improving the activity of the main catalyst, and improving the polymerization reaction kinetics of the main catalyst. The obtained polymer product has the characteristics of narrow molecular weight distribution and high melt index.

[0121] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. A spherical catalyst component for propylene polymerization, comprising a solid titanium main catalyst, an alkyl aluminum compound co-catalyst and an external electron donor compound; characterized in that: The solid titanium main catalyst comprises any one of magnesium or magnesium halide or alkyl magnesium or alkoxy magnesium or a mixture of two or more thereof, a liquid titanium compound and an internal electron donor compound; The internal electron donor compound is selected from one or more compounds having the structure of formula (I): In the formula, R is selected from H atoms, halogens, C1~C 20 The term "alkyl" refers to a linear or branched alkyl, alkenyl, cycloalkyl, aryl, arylalkyl or alkylaryl group.

2. A spherical catalyst component for propylene polymerization according to claim 1, characterized in that: The alkyl aluminum compound co-catalyst has the general formula of AlR 1 n X 3-n , where R 1 Is the same or different C1~C 20 Alkyl, including linear, branched or cyclic alkyl, X is halogen, n = 1, 2 or 3; The external electron donor compound is a compound of the general formula R n Si(OR ’ ) 4-n An organosilicon compound, wherein 0≤n≤3, R and R ’ are the same or different alkyl, cycloalkyl, aryl, or halogenated alkyl groups; or, R is a halogen or a hydrogen atom.

3. A spherical catalyst component for propylene polymerization according to claim 1, characterized in that: The ratio between the solid titanium main catalyst, the alkyl aluminum compound co-catalyst and the external electron donor compound is calculated based on the molar ratio of titanium, the amount of the alkyl aluminum compound co-catalyst is 5 to 1000 moles; and the amount of the external electron donor compound is 0.025 to 1.0 mole based on the molar ratio of aluminum.

4. A spherical catalyst component for propylene polymerization according to claim 1, characterized in that: The magnesium is micron-sized spherical magnesium particles; the magnesium halide is selected from magnesium dihalide, water or alcohol complex of magnesium dihalide, and a derivative of magnesium dihalide in which a halogen atom is replaced by a hydrocarbon group or a hydrocarbon oxy group in the molecular formula; the alkyl magnesium includes diethyl magnesium, di-n-butyl magnesium, and di-n-hexyl magnesium, and the alkoxy magnesium includes ethoxy magnesium; The liquid titanium compound should be a liquid compound that is completely soluble in a non-polar solvent at the application temperature. The general formula of the liquid titanium compound is Ti(OR): 4-a X a , in the general formula, R is C1~C 10 wherein X is selected from F, Cl, and Br, and a is an integer of 1 to 4. The amount thereof is 0.5 to 150 moles per mole of magnesium halide.

5. A spherical catalyst component for propylene polymerization according to claim 2, characterized in that: The alkyl aluminum compound co-catalyst is selected from any one of triethyl aluminum, triisobutyl aluminum, tri-n-butyl aluminum, tri-n-hexyl aluminum, and alkyl aluminum chloride, or a mixture of two or more thereof.

6. A spherical catalyst component for propylene polymerization according to claim 4, characterized in that: The magnesium halide is selected from any one of magnesium dichloride, magnesium dibromide, phenoxymagnesium chloride, isopropoxymagnesium chloride, and butoxymagnesium chloride, or a mixture of two or more thereof; The liquid titanium compound is selected from any one of titanium tetrachloride, titanium tetrabromide, titanium tetraiodide, titanium tetrabutoxide, titanium tetraethoxide, titanium triethoxide monochloride, titanium diethoxide dichloride, titanium triethoxide monochloride, or a mixture of two or more thereof; The internal electron donor compound is selected from any one of benzoic acid peroxide, methyl perbenzoate, ethyl perbenzoate, isopropyl perbenzoate, tert-butyl perbenzoate, tert-hexyl perbenzoate, and tert-amyl perbenzoate, or a mixture of two or more thereof; the internal electron donor compound is used in an amount of 0.10 to 0.50 mole per mole of magnesium halide.

7. A solid titanium main catalyst for propylene polymerization or copolymerization, characterized in that: It comprises any one or a mixture of two or more of magnesium or magnesium halide or alkyl magnesium or alkoxy magnesium, a liquid titanium compound and an internal electron donor compound; wherein the internal electron donor compound is selected from one or more compounds having a structure of formula (I): In the formula, R is selected from H atoms, halogens, C1~C 20 The term "alkyl" refers to a linear or branched alkyl, alkenyl, cycloalkyl, aryl, arylalkyl or alkylaryl group.

8. A solid titanium main catalyst for propylene polymerization or copolymerization according to claim 7, characterized in that: The solid titanium main catalyst also includes an alkyl aluminum compound, and the alkyl aluminum compound includes trimethyl aluminum, triethyl aluminum, triisobutyl aluminum, and diethyl aluminum monochloride.

9. The method for preparing the solid titanium main catalyst according to claim 7 or 8, characterized in that: The method comprises the following steps: Step 1. dissolving any one of magnesium, magnesium halide, alkyl magnesium or alkoxy magnesium, or a mixture of two or more thereof in a solvent system containing an organic alcohol to form a uniform solution; Step 2. Adding a liquid titanium compound, the contact reaction temperature of the liquid titanium compound and the magnesium halide solution is controlled at -40 to 0°C to ensure that the titanium / magnesium active component is a uniform solution, and the amount of the titanium compound added is 1 to 50 mol per mole of magnesium halide; Step 3. The mixed solution of step 2 is heated, and an internal electron donor compound for adjusting the activity of the catalyst, hydrogen sensitivity and polymer regularity is added, and then an alkyl aluminum compound is added or not added, and the temperature is continued to be heated, and solid titanium main catalyst particles are precipitated by stirring, so that the titanium content in the obtained solid titanium main catalyst is between 0.5 and 4.0%; the magnesium content is between 5.0 and 20.0%; and the content of the internal electron donor compound is between 5.0 and 15.0%; or, Step 1. dissolving any one of magnesium or magnesium halide or alkyl magnesium or alkoxy magnesium or a mixture of two or more thereof in a solvent system containing an organic alcohol to form a uniform solution; then adding an internal electron donor compound for adjusting the activity of the catalyst, hydrogen sensitivity and polymer regularity to the uniform solution; Step 2. Adding a liquid titanium compound, the contact reaction temperature of the liquid titanium compound and the magnesium halide solution is controlled at -40 to 0°C to ensure that the titanium / magnesium active components are a uniform solution, and the amount of the titanium compound added is 1 to 50 mol per mole of magnesium halide; Step 3. Heat the mixed solution of step 2, add or not add an alkyl aluminum compound, then continue to heat it, stir and precipitate solid titanium main catalyst particles, so that the titanium content in the obtained solid titanium main catalyst is between 0.5 and 4.0%; the magnesium content is between 5.0 and 20.0%; and the content of the internal electron donor compound is between 5.0 and 15.0%.

10. Use of the spherical catalyst component for propylene polymerization according to any one of claims 1 to 6 or the solid titanium main catalyst for propylene polymerization or copolymerization according to claim 7 or 8 in the polymerization reaction of olefins CH2=CHR, wherein R is hydrogen or an alkyl or aryl group with 1 to 6 carbon atoms.

Citation Information

Patent Citations

  • Solid titanium catalyst, preparation method and catalyst component for propylene polymerization

    CN114957519A

  • Propylene polymerized catalyst system, preparationmethod and usage

    CN1539857A

  • Olefin polymerization catalyst, method for producing the same, and its applications

    JP2014512439A

  • Method for producing propylene polymer having a high melt-flowability

    KR1020090059562A